Reflective practice enhances osteopathic clinical reasoning. (September 2019) - McIntyre, Cindy; Lathlean, Judith; Esteves, Jorge E.
Abstract: Background : There has been extensive research of clinical reasoning in health professions, and reflective practice is widely used. However, in the field of osteopathy, clinical reasoning is largely under-researched and the use of structured reflective practice at its early stages. Objective : To understand the broad role of reflective practice on osteopathic clinical reasoning during active delivery of patient care. Method : Using an ethnographic method, the diagnostic and reasoning processes of one osteopath were recorded as they arose. These notes were then expanded to give a description of the interaction with the patient during the clinical encounter. Using autoethnography and reflective practice, the descriptions of the clinical encounters were developed into reflective narratives which were then analysed using elements originating from grounded theory. Results : Reflective practice helps the practitioner become aware of their moment-by-moment osteopathic practice, it triggers the questioning of a practitioner's clinical reasoning, and creates change of practice. Conclusion : This novel study highlights the relevance of reflective practice as a means of monitoring the thinking and reasoning processes in osteopathy. An increase in awareness of clinical reasoning processes could help prevent cognitive and affective biases and possible clinical error. We would argue that reflective practice is a critical tool in maintaining professional competence in osteopathy across a practice lifetime. Highlights: Reflection underpins all osteopathic practice and CPD. Reflective practice and knowledge of metacognition may help prevent error and bias. Reflective practice facilitates practitioners to improve patient care. Reflective practice should improve practitioner wellness and job satisfaction.